2012
DOI: 10.1159/000338669
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Subtypes and Signal Transduction Mechanisms Contributing to the Estrogenic Attenuation of Cannabinoid-Induced Changes in Energy Homeostasis

Abstract: We examined the receptor subtypes and signal transduction mechanisms contributing to the estrogenic modulation of cannabinoid-induced changes in energy balance. Food intake and, in some cases, O2 consumption, CO2 production and the respiratory exchange ratio were evaluated in ovariectomized female guinea pigs treated s.c. with the cannabinoid receptor agonist WIN 55,212-2 or its cremephor/ethanol/0.9% saline vehicle, and either with estradiol benzoate (EB), the estrogen receptor (ER) α ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 68 publications
(109 reference statements)
3
31
1
Order By: Relevance
“…In Hec50 endometrial cancer cells (ER-negative/GPER-positive) several compounds initiated GPER-mediated PI3K and ERK1/2 activation, including E2, G-1, 4OHT, RAL, ICI, as well as PPT (with submaximal effects for PPT observed at 10 nM). This report provided the first evidence that PPT also functions as a GPER agonist at higher concentrations, demonstrating that although PPT remains selective for ERa over both ERb and GPER, care must be taken in the interpretation of results employing receptor-selective ligands, particularly with respect to the concentrations and doses of these compounds used in experimental systems (Washburn et al, 2013). Notably, the ERaselective antagonist (methyl-piperidino-pyrazole) (Sun et al, 2002;Harrington et al, 2003), which has not been as widely used as PPT, has not been evaluated for selectivity toward GPER.…”
Section: G Estrogen Receptor-selective Ligandsmentioning
confidence: 94%
“…In Hec50 endometrial cancer cells (ER-negative/GPER-positive) several compounds initiated GPER-mediated PI3K and ERK1/2 activation, including E2, G-1, 4OHT, RAL, ICI, as well as PPT (with submaximal effects for PPT observed at 10 nM). This report provided the first evidence that PPT also functions as a GPER agonist at higher concentrations, demonstrating that although PPT remains selective for ERa over both ERb and GPER, care must be taken in the interpretation of results employing receptor-selective ligands, particularly with respect to the concentrations and doses of these compounds used in experimental systems (Washburn et al, 2013). Notably, the ERaselective antagonist (methyl-piperidino-pyrazole) (Sun et al, 2002;Harrington et al, 2003), which has not been as widely used as PPT, has not been evaluated for selectivity toward GPER.…”
Section: G Estrogen Receptor-selective Ligandsmentioning
confidence: 94%
“…In previous studies, the Gq-mER ligand STX showed a clear anorectic effect in female guinea pigs (37,50). Since our in vitro experiments suggested that STX would also be anorectic in males, we wanted to compare food intake in both sexes.…”
Section: Methodsmentioning
confidence: 99%
“…Wortmannin (PI3K inhibitor, Sigma), LY-294002 (PI3K inhibitor; EMD Millipore, Billerica, MA), and TGX-221 [P13K p110␤ subunit inhibitor; 7-methyl-2-morpholino- Feeding experiments. We chose to use guinea pigs for the feeding experiments on the basis of our previous publications that the diphenylacrylamide compound STX decreases food intake and weight gain following ovariectomy in females (32,37,50) and the fact that STX is bioavailable (F ϭ 22%) and centrally active in the female guinea pig (35). For the feeding studies, a Comprehensive Lab Animal Monitoring Systems (CLAMS; Columbus Instruments, Columbus, OH) recorded daily food intake in adult gonadectomized male (n ϭ 10) and female guinea pigs (n ϭ 12) as previously described (35).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations